Unveiling the Morphology of Saharan Heritage: Exploring Urban Heritage in the Algerian Sahara - Halima Gherraz; Imen Guechi; Djamel Alkama (Indonesian Journal of Social Science Research, 2023)
This study is dedicated to exploring the Ksurian heritage of the Algerian Sahara, aiming to reveal the abundance and variety embedded within each ksar. Employing a comprehensive analytical approach, we meticulously examine four fundamental aspects: the urban layout, the dwellings, the materials utilized, and the construction techniques employed. To accomplish this research, extensive field visits were conducted, encompassing photography, on-site surveys, and engaging discussions with experts to gain profound insights into the distinctive characteristics of each region. Our findings unveil a remarkable and diverse heritage, exhibiting variations from one region to another, ultimately reflecting the unique traditions and capabilities of the Saharan population.